Kajian Pemanfaatan Fitur dan Fasilitas Moodle dan Office-365 untuk Peningkatan Kualitas Pembelajaran pada Tutorial Online - Adhi Susilo; Deddy Ahmad Suhardi (Universitas Negeri Malang, 2018)
Abstrak: E-learning merupakan singkatan dari electronic learning, merupakan cara baru dalam proses belajar mengajar yang menggunakan media elektronik khususnya internet sebagai sistem pembelajarannya Universitas Terbuka (UT) memiliki aplikasi e-learning yang di beri nama Tuton (tutorial online) Sistem pembelajaran jarak jauh yang di gunakan UT sekarang sangat membantu dosen dan mahasiswa dalam proses belajar dengan memanfaatkan teknologi yang sudah maju seperti sekarang ini. Pada studi ini, kami mencoba menganalisis persepsi mahasiswa dan tutor dalam pemanfaatan fitur dan fasilitas Office 365 dalam tuton dan praktek online. Berdasarkan hasil pembahasan diperoleh kesimpulan bahwa Tanggapan terhadap perlu tidaknya fitur dipengaruhi oleh usia, gender, pendidikan, pelatihan tuton, dan aktivitas tuton. Kecuali pada fasilitas konferensi online dan berbagi cerita digital, tanggapan terhadap perlu tidaknya fasilitas dipengaruhi usia, gender, pendidikan, pekerjaan, pelatihan dan atau aktivitas tuton. Oleh karena itu, rekomendasi yang kami ajukan adalah diperlukan adanya kegiatan yang dirancang untuk mencapai optimalisasi pembelajaran jarak jauh antara lain penguatan lingkungan tuton dan prakton, perlunya peningkatan kompetensi TIK staf akademik dan keterlibatannya dalam tuton/prakton, perlunya peningkatan kapasitas pelayanan prima kepada semua pemangku kepentingan UT dan pengembangan dan peningkatan pelatihan penggunaan aplikasi standar dalam Moodle dan Office365 agar bisa saling melengkapi.Abstract: One of the main means to enhance student’s learning activities is by implementing technology in their learning activities. Nowadays, many universities in the world had applied this method due to many benefits that its offer. Universitas Terbuka (UT) is one of distance learning institution in Indonesia that had applied this method for its student. Therefore, this research intends to investigate the perceptions of students and tutors in utilizing the features and facilities of Office365 in online tutorial and online practicum. Furthermore, the perceptions of students and tutors that was analyzed include the use of standard applications contained in Moodle and their expectations in utilizing Office365 features and facilities for online tutorials and online practicum. This study employs online survey that consists of 11 items. The perception of student regarding the Office365 features is influenced by age, gender, education, online tutorial training, and online tutorial activities. The students’ responses of Office365 facilities are affected by age, gender, education, employment, training and online tutorial activities. Office365’s features and facilities are most likely to influence the effectiveness of the distance learning process since students have the opportunity to interact with their teachers, peers, and learning materials. Moreover, the Office365 enable student to access the material through this facility. The other benefit is the existence of forum that could be used as discussions means between student and lecturer. Hence we recommend that all online activities should be designed to achieve the optimization of distance learning such as strengthening the online tutorial and online practicum, improving the ICT competence of academic staff and their involvement in online tutorial and online practicum, improving services to all UT’s stakeholders and developing an upgrade of standard application training of Moodle and Office365